Philosophy : A Very Short Introduction - Craig, Edward, 1942- (Karachi, Pakistan Oxford University Press, 2009)
Edward Craig argues that philosophy is not an activity from another planet: learning about it is just a matter of broadening and deepening what most of us do already. He shows that philosophy is no mere intellectual pastime: thinkers such as Plato, Buddhist writers, Descartes, Hobbes, Hume, Hegel, Darwin, Mill, and de Beauvoir were responding to real needs and events - much of their work shapes our lives today, and many of their concerns are still ours.
Include Colour Illustration and Index
Keywords: Philosophy